Addressing Bias among Medical Care Teams on the Wards: A Perspective from Asian Medical Students in the United States - Jesper Ke; Ellen Zhang; Kate Lee; Hueyjong Shih; Chin Hur (University Library System, University of Pittsburgh, 2023)
This piece provides a personal perspective of the bias that affects Asian-American medical students in the United States in the clinical wards. In the evolving landscape of medical education, discussions about race, professionalism, and structural change have come to the forefront, especially with regards to patient interactions. However, less has been discussed about bias that may be perpetuated within a clinical team: between medical students, residents, and faculty physicians. This piece builds on these personal experiences to highlight some steps that can range from the individual to institutional level to address some of these biases, especially as it pertains to Asian-American Medical Students. Overall, this piece shares perspectives that draw strongly on personal experiences in the hopes of creating change for both colleagues and aspiring physicians across the medical spectrum.